Influence of temperature and variety on seed germination of soybean (Glycine max L. Merr) at different germination times - Abd Ghani, Rosnani; Jolánkai, Márton; Omar, Suhana; Khalid, Noriza; Tarnawa, Ákos (Acta Agraria Debreceniensis, 2023)
Seed germination is an important stage in crop development that affects plant performance, crop yield, and quality. Many factors influence seed germination, and one of the most important factors is temperature. The closer the temperature is to the optimum, the faster germination will occur. Temperature affects seed germination in various plants and varies depending on the variety. Therefore, the effect of temperature on seed germination is necessary to investigate, also for soybean varieties. Soybean is one of the world's most valuable oil-seed crops. Generally, proper seedling establishment and germination of soybean seeds are crucial processes in the survival and growth cycle of the crop. Thus, a study was done to investigate the influence of temperature and variety on soybean seed germination at different times after sowing. The experiment was carried out at the Institute of Agronomy, Hungarian University of Agriculture and Life Sciences (MATE), Crop Production Laboratory. Seeds of two soybean varieties were subjected to three different temperatures: 15, 25, and 35 °C, and two soybean varieties, Martina and Johanna were tested. There were four germination times based on the days after sowing: Days 3, 5, 7, and 9. This experiment was set up with a completely randomized block design and four replications. According to the findings of this study, the Martina variety showed a better germination rate as well as higher vigor and viability than the Johanna variety in the first 12 days after sowing. At temperatures of 15 °C and 25 °C, both varieties achieved comparable percentages of viability, but they were more vigorous at 25 °C due to better total seedling length. Thus, the information gained from this study will indirectly determine and confirm the proper temperature for the initial growth of the Martina and Johanna varieties.